Intelligent computer mathematics : 11th International Conference, CICM 2018, Hagenberg, Austria, August 13-17, 2018, Proceedings /: 11th International Conference, CICM 2018, Hagenberg, Austria, August 13-17, 2018, Proceedings. (2018) - Unknown
No abstract available